Design and performance study of truncated CPC by eliminating multiple reflections of solar radiation in hybrid CPV/T system: Highest and lowest truncation position. (15th October 2016) - Xie, Huling; Wei, Jinjia; Wang, Zexin; Liu, Zhibing; Gao, Yang; Ma, Qiuming; Zhang, Gaoming
Highlights: A truncated CPC called LEMR was designed by eliminating multiple reflections. Comparative research between HEMR and LEMR is carried out by theoretical analysis. The tradeoff between cost and optical performance of LEMR is better than HEMR. Abstract: The height of conventional compound parabolic concentrator (CPC) increase greatly with increasing geometric concentration ratio, resulting in large reflector consumption and deteriorative optical performance. A new truncated CPC with highest truncation position called HEMR was proposed in the previous study (Xie et al., 2016), which can improve the tradeoff between cost reduction and optical performance. In order to further improve the tradeoff to make the CPC more competitive in the commercial field, the truncated CPC with lowest truncation position called LEMR is designed by eliminating multiple reflections in the present study, and the performance is researched by the material consumption assessment and Monte-Carlo simulation theoretically under the conditions of 156 mm wide best concentration plane and 4 times geometric concentration ratio. The results show that the material consumption of LEMR is about 80% of HEMR while the optical performance including uniformity and optical efficiency is almost the same as HEMR, indicating that LEMR has a better tradeoff between cost reduction and optical performance and thus has more extensive application potential.